2005
DOI: 10.1016/j.ymthe.2005.07.524
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Inhibition of HIV-1 Infection in Primary Hematopoietic Cells by Lentiviral Vector Delivery of a Triple Combination of Anti-HIV shRNA, Anti-CCR5 Ribozyme, and a Nucleolar-Localizing TAR Decoy

Abstract: Combinatorial therapies for the treatment of HIV-1 infection have proven to be effective in reducing patient viral loads and slowing the progression to AIDS. We have developed a series of RNA-based inhibitors for use in a gene therapy-based treatment for HIV-1 infection. The transcriptional units have been inserted into the backbone of a replication-defective lentiviral vector capable of transducing a wide array of cell types, including CD34+ hematopoietic progenitor cells. The combinatorial therapeutic RNA ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
190
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(193 citation statements)
references
References 45 publications
2
190
0
1
Order By: Relevance
“…The concern of partial protection from viral infection has been noted for CCR5 disruption mechanisms when used individually to protect T cells, such as short hairpin RNA, ribozymes or intrabodies, when higher viral challenge amounts were used. 17,18,61 A possible explanation for the enhanced efficacy of the CCR5 intrabody in our studies could lie in the coupling of the KDEL sequence with a high-affinity intrabody. 16,25 The use of the KDEL allows efficient intrabody trapping of both recycled and newly expressed receptor in the endoplasmic reticulum, thereby enhancing CCR5 loss at the cell surface.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 88%
“…The concern of partial protection from viral infection has been noted for CCR5 disruption mechanisms when used individually to protect T cells, such as short hairpin RNA, ribozymes or intrabodies, when higher viral challenge amounts were used. 17,18,61 A possible explanation for the enhanced efficacy of the CCR5 intrabody in our studies could lie in the coupling of the KDEL sequence with a high-affinity intrabody. 16,25 The use of the KDEL allows efficient intrabody trapping of both recycled and newly expressed receptor in the endoplasmic reticulum, thereby enhancing CCR5 loss at the cell surface.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 88%
“…56 Recently, Rossi described a triple-element combinatorial therapeutic RNA vector that harbors: (1) a U6 Pol III promoterdriven short hairpin RNA specific for rev and tat mRNAs; (2) a U6 transcribed nucleolar-localizing TAR RNA decoy; and (3) a VA1-derived Pol III cassette that expresses an antiCCR5 ribozyme. 55 HIV replication was inhibited by this 'triple-threat' approach and illustrates further the feasibility of combinatorial RNA-based gene therapy for HIV infection (Figure 3). In addition, these results highlight the potential of inhibitory RNAs in stem cell-based gene therapy for HIV/AIDS.…”
Section: Aptamers For Intracellular Targets Are Being Developedmentioning
confidence: 68%
“…[52][53][54] A lentiviral-based construct that harbored both a CCR5 ribozyme that downregulates HIV-1 cell surface coreceptor, and a U16TAR decoy, which inhibits viral Tat-activated transcription, was shown provide a high degree of resistance against HIV-1 in both primary and CD34(+)-derived monocytes. 38,55 A similar effect was obtained with a combinatorial construct harboring an antiCCR5 ribozyme (as well as ribozymes targeted to viral mRNAs coding for tat, rev and env proteins), a rev RNA decoy, and an siRNA directed against a sequence common to rev and tat mRNAs. 56 Recently, Rossi described a triple-element combinatorial therapeutic RNA vector that harbors: (1) a U6 Pol III promoterdriven short hairpin RNA specific for rev and tat mRNAs; (2) a U6 transcribed nucleolar-localizing TAR RNA decoy; and (3) a VA1-derived Pol III cassette that expresses an antiCCR5 ribozyme.…”
Section: Aptamers For Intracellular Targets Are Being Developedmentioning
confidence: 71%
“…2,3 Several groups including our own have shown that siRNAs targeted to human immunodeficiency virus-1 (HIV-1) genome or its receptor CCR5 specifically suppress HIV-1 replication in T cells and macrophages. [4][5][6] In these studies, a general adopted approach is to stably express in the target cell a short hairpin RNA (shRNA) that can be processed into siRNA by endogenous RNase III-like enzyme Dicer in the cytoplasm. [7][8][9][10][11] Most studies used polymerase (pol) III promoters to control the expression of the shRNA gene.…”
Section: Introductionmentioning
confidence: 99%